(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
In recent years, the education system in Uzbekistan has faced unprecedented challenges due to rapid demographic growth, resulting in severe school capacity deficits and increased pressure on educators. Traditional administrative management methods are no longer sufficient to handle this demographic burden